Idealização e colonização na obra Iracema de José de Alencar: a simbologia dos personagens Iracema e Martim - PIRES, Cláudia Rodrigues (2023)
The present work has a bibliographical research conception and if will focus on the symbolic analysis of the characters Iracema, a warrior Indian, gentle and strong, and Martim the white colonizer in the work Iracema by author José de Alencar. Thus, through a descriptive and interpretative analysis, will verify which are the important factors for these two characters to are characterized as representing the unexplored land and war and destruction respectively, in order to understand the importance of Alencar mixes fiction and history, using two unique characters to demonstrate, in a romanticized and symbolic way, how this contact between the Indians and whites during Brazilian colonization, definitively affected the future of the population, both indigenous and white. For this purpose, it will be used as based on the ideas of Machado de Assis, Alfredo Bosi, Ricupero, Pinto, Antônio Candido, Ribeiro, among others.